Dissection of full-length transcriptome and metabolome of Dichocarpum (Ranunculaceae): implications in evolution of specialized metabolism of Ranunculales medicinal plants - Hao,Da-Cheng; Li,Pei; Xiao,Pei-Gen; He,Chun-Nian (PeerJ, 2021)
Several main families of Ranunculales are rich in alkaloids and other medicinal compounds; many species of these families are used in traditional and folk medicine. Dichocarpum is a representative medicinal genus of Ranunculaceae, but the genetic basis of its metabolic phenotype has not been investigated, which hinders its sustainable conservation and utilization. We use the third-generation high-throughput sequencing and metabolomic techniques to decipher the full-length transcriptomes and metabolomes of five Dichocarpum species endemic in China, and 71,598 non-redundant full-length transcripts were obtained, many of which are involved in defense, stress response and immunity, especially those participating in the biosynthesis of specialized metabolites such as benzylisoquinoline alkaloids (BIAs). Twenty-seven orthologs extracted from trancriptome datasets were concatenated to reconstruct the phylogenetic tree, which was verified by the clustering analysis based on the metabolomic profile and agreed with the Pearson correlation between gene expression patterns of Dichocarpum species. The phylogenomic analysis of phytometabolite biosynthesis genes, e.g., (S)-norcoclaurine synthase, methyltransferases, cytochrome p450 monooxygenases, berberine bridge enzyme and (S)-tetrahydroprotoberberine oxidase, revealed the evolutionary trajectories leading to the chemodiversity, especially that of protoberberine type, aporphine type and bis-BIA abundant in Dichocarpum and related genera. The biosynthesis pathways of these BIAs are proposed based on full-length transcriptomes and metabolomes of Dichocarpum. Within Ranunculales, the gene duplications are common, and a unique whole genome duplication is possible in Dichocarpum. The extensive correlations between metabolite content and gene expression support the co-evolution of various genes essential for the production of different specialized metabolites. Our study provides insights into the transcriptomic and metabolomic landscapes of Dichocarpum, which will assist further studies on genomics and application of Ranunculales plants.
Keywords: Dichocarpum; Full-length transcriptome; Metabolome; Gene duplication; Phylogenomics; Ranunculales